Virtual/Mixed/Augmented Reality Laboratory Research for the Study of Augmented Human and Human-Machine Systems - Helin, Kaj; Karjalainen, Jaakko; Kuula, Timo; Philippon, Nicolas (Proceedings (International Conference on Intelligent Environments), 2016)
In this work we introduce a new research concept called Augmented Human, and consider how it may benefit from prior research efforts. In essence, the paper describes the long research history of a specific Virtual/Mixed/Augmented Reality (VR/MR/AR) laboratory and reflects how it may well be employed as a premise for Augmented Human research and the design of new human-machine systems. The paper briefly describes how constitutive laboratory research has already been employed for some years in more than a hundred company cases, which have exploited participatory design and human-centered design for the human-machine system development. The paper describes further how the latest cases have moved closer to the human boundary level and thus oriented towards Augmented Human research. This fifth generation VR/MR/AR/AH laboratory has taken the form of an open cave-like environment with a motion platform, 3D sound, haptics, VR/AR Head-mounted displays and physical objects.